2021
DOI: 10.26418/jppk.v11i1.51824
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Variasi Latihan Terhadap Hasil Shooting Dalam Permainan Sepak Bola

Abstract: This study aims to improve the basic technique of shooting at the goal in a soccer game with a variety of exercises for players or players who take part in soccer extracurriculars at SMA N 8 Pontianak. -post test design and use shooting test instruments at the goal. The sample of this study was all football players who took part in extracurricular football at SMA N 8 Pontianak, totaling 20 people with the technique of saturated sampling technique. Based on the results of the research, the initial test shooting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Basic techniques in shooting must be considered when shooting, starting from the starting position, and carrying out the motion to the end of the movement so that the shooting can be directed properly. Good technique is needed to shoot optimally and the right learning method is needed to achieve good technique (Ardian et al, 2019;Masyni & Triyono, 2018;Hasrion et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic techniques in shooting must be considered when shooting, starting from the starting position, and carrying out the motion to the end of the movement so that the shooting can be directed properly. Good technique is needed to shoot optimally and the right learning method is needed to achieve good technique (Ardian et al, 2019;Masyni & Triyono, 2018;Hasrion et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Within 90 minutes the team that can score the most goals than the team is declared the winner (Dhimas et al, 2020). Achieving the goal of the game of football requires teamwork (Sudirman et al, 2022), good basic football techniques need to be mastered and trained regularly, purposefully and repeatedly by football players to get good technical skills, one of the techniques is the shooting technique (Santosa & Ishak, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that affect endurance can be heredity, age, gender, aerobic capacity, anaerobic capacity, and physical activity (Prananda & Yanti, 2021). Another study conducted on young football athletes at the Real Madrid Football School and Baturetno Football School showed that athletes had poor knowledge about the nutritional and fluid requirements for young football athletes at the Real Madrid Football School and Baturetno Football School (Puspaningtyas et al, 2019).…”
Section: Figure 2 Physical Condition (Vo2max) Of Pusaka Fc Club Ball ...mentioning
confidence: 99%
“…Permainan target adalah permainan dimana pemain akan mendapatkan skor apabila bola ditendang dengan terarah mengenai sasaran yang telah ditentukan dan semakin sedikit tendangan menuju sasaran semakin baik (Faisal, 2018;Lumbantoruan et al, 2021). Permainan target dapat digunakan untuk membantu pemain melatih konsentrasi dan ketepatan target sehingga pemain dapat terlatih untuk melakukan Shooting kearah sasaran secara tepat (Hanafi, 2020;Wibawa, 2017).…”
unclassified